STRATEGI PENINGKATAN BUDAYA BACA PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMK HARAPAN MEKAR II - Maipuja, Dira (Universitas Dharmawangsa, 2024)
The culture of reading is both a prerequisite and a characteristic of the progress of a nation or society. An advanced nation or society places the habit of reading as one of the necessities of life. The approach taken in this research is a qualitative approach. A qualitative approach is a way of understanding a phenomenon as a distinctive uniqueness in a particular situation with various interaction complexities. In the strategy carried out by the teachers of SMK Harapan Mekar 2, the teachers give assignments to the students, one of which assigns students to look for information either from newspapers, magazines, the internet or from reading books in this task, students will carry out the assigned tasks and will become interested in reading so that reading students will grow and develop.